STRATEGI REFORMASI BIROKRASI PEMERINTAHAN DAERAH: MENUJU ERA GLOBALISASI - Rohayatin, Titin - (Faculty of Social and Political Science Universitas Brawijaya, 2017)
Strategy of bureaucracy reform in local government is an effort and a step to strengthen locality and to solve many challenges in globalization era. Bureaucracy reform is not only to simplify bureaucracy structure but also to change mind set and work culture in bureaucracy, particularly in administrative management of local government. Bureaucracy reform had launched since reformation era, but it has faced impediment and challenge such as bad bureaucrat behavior, many corrupt bureaucrats, bad public service even though decentralization has been objectified. Performance problem has not been better yet even performance indicator has been available. Therefore, bureaucracy reform conceptual model as guideline in structure improvement, work culture of local bureaucracy, and strategy of bureaucracy reform consisting steps of bureaucracy improvement are important thing. As a result, there are general direction or strategy of bureaucracy reform as guideline for improvement of structure, performance, and culture in local bureaucracy, particularly local government, Cimahi city.